The Efforts of ‘Pendidikan Agama Islam’ Teachers in Classroom Management During Covid-19 Pandemic: (at SMPIT Nurul Fikri Tulungagung) - Moch. Rizal Fuadiy; Nanda Nurlaili (Tarbiyah Departement collaboration with AMCA, 2020)
During the Covid-19 pandemic, the Government through the Menteri Pendidikan dan Kebudayaan (Minister of Education and Culture) instructed all educational institutions to carry out distance learning. The purpose of this study was to determine the efforts of the Islamic Pendidikan Agama Islam teacher in implementing distance learning. The method approach used is qualitative. The results of field research indicate that Islamic Religious Education teachers have difficulty implementing learning, because educational institutions are not ready to support the distance learning process. Learning is done through a social media software application, because it is easy to use and all parents of students must have it. The teacher conveys the learning content then students respond by sending the results of assignments based on Student Worksheets via social media.